Pālāḻimathanaṃ āṭṭakkatha - Sarōjini, Pi. Pi (Tiruvanantapuraṃ Malayāḷagranthāvali ;, 1982)
Anonymous libretto for Kathakali, classical dance-drama of Kerala, based on an episode from the Bhāgavatapurāṇa.